Iatrogenic hydronephrosis after ovariosalpingohysterectomy therapeutic correction (Research, Society and Development, 2023)
The ovariosalpingohysterectomy (OSH) is a relatively safe procedure. However, an iatrogenic is described to accidental ligature or traumatic of ureter, which could result to hydronephrosis, a disease due to superior urinary tract. The article has a objective to describe the case of a canine submitted to ureteroneocystostomy due to iatrogenic hydronephrosis after OSH. Was attend a canine, female, eight years old weighing 22kg, presenting urinary incontinence and nocturia. The patient underwent to a procedure of OSH five months ago, started to manifest symptoms of heat cycle after surgery. At the ultrasound exam found a remnant ovary syndrome and pyometritis in uterine colon, being subjected to a therapeutic approach OSH. Past some days, with new symptoms the ultrasonic exam has revealed a hydronephrosis of the right kidney and right hydroureter. The procedure was successfully done with no intercurrence. In spite of OSH has a very low casuistry of complications, when then occurs, the correct diagnosis due to right treatment is primordial to health and stabilization of the animal.